Can a “Zero Land Use” Diet Maintain Milk Production of Dairy Cows? - C. S. Takiya; C. M. Ylioja; A. Bennett; M. Davidson; B. J. Bradford (Kansas Agricultural Experiment Station Research Reports, 2018)
Dairy cows can convert feeds unsuitable and unpalatable for humans into milk and play a key role in food security. Feed efficiency is usually calculated as the ratio between nutrients secreted in milk and nutrient intake, but this metric does not address concerns about human/livestock feed competition. This study aimed to evaluate whether cows fed a “zero land use” diet (diet that does not affect land used for production of human food), with or without rumen-protected amino acids, can maintain milk compared to a conventional lactation diet. Twelve second-lactation dairy cows were used in a 3×3 Latin square design experiment to evaluate 1) conventional total mixed ration (TMR) for lactating cows (CON), containing 25.7% byproduct feeds; 2) a TMR comprised of zero land use feedstuffs (ZLU); and 3) ZLU with top-dressed rumen-protected amino acids (ZLU-AA). Cows fed ZLU or ZLU-AA diets consumed less dry matter (P<0.01) and decreased (P<0.01) milk and energy-corrected milk yield of cows. Feed efficiency was similar between cows fed CON and ZLU but it was reduced (P<0.01) when cows were fed ZLU-AA. In a scenario reflecting current food system byproduct use, cows fed ZLU diets showed greater (P<0.01) human-edible metabolizable energy and protein recovery in milk than cows fed CON. Zero land use diets did not maintain milk production of late-lactation cows either with or without rumen-protected amino acids.
Keywords: byproduct; human-edible food; sustainability